2020
DOI: 10.3390/resources9030034
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of the Closed-Loop Recycling of Used Disposable Diapers

Abstract: In Japan, approximately 23.5 billion paper diapers are produced annually (total of diapers for infants and adults produced in 2018). The majority of used paper diapers are disposed of through incineration; in certain regions, some paper diapers are recycled, mostly by open-loop recycling or thermal recycling. To date, several methods of recycling used paper diapers have been proposed and developed, but these methods are considered to have different types and amounts of recycled materials and different environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Some literature reported other methods for slurry sterilisation. One of them is done by ozone which is effective to sterilise the slurry and increases the brightness of recycled fibre obtained [10,13,14]. The separation process of fibre and SAP gel manually also needs to be evaluated, since it is low in productivity and risks to the workers' health.…”
Section: Description Of the Recycling Process At Bsbmentioning
confidence: 99%
“…Some literature reported other methods for slurry sterilisation. One of them is done by ozone which is effective to sterilise the slurry and increases the brightness of recycled fibre obtained [10,13,14]. The separation process of fibre and SAP gel manually also needs to be evaluated, since it is low in productivity and risks to the workers' health.…”
Section: Description Of the Recycling Process At Bsbmentioning
confidence: 99%
“…Recycling of disposable diapers ensures environmental sustainability by substituting raw material inputs and reducing the cost of waste output on the economic system. Itsubo et al (2020) reported the recycling of pulp and SAP from used disposable diapers into their virgin state. The recycling method developed by Itsubo et al (2020), demonstrated a reduction in GHG emissions from landfills and incineration processes by 47% and 39% respectively.…”
Section: Recyclingmentioning
confidence: 99%
“…Itsubo et al (2020) reported the recycling of pulp and SAP from used disposable diapers into their virgin state. The recycling method developed by Itsubo et al (2020), demonstrated a reduction in GHG emissions from landfills and incineration processes by 47% and 39% respectively. However, Itsubo et al (2020), could not ascertain the economic rationality of this method as no comparative study on costs had been conducted.…”
Section: Recyclingmentioning
confidence: 99%
“…A typical SAP is highly hydrophilic networks that can imbibe to other plastics, DHCPs, together with SAPs in the inner layers, are usually heavily contaminated after use with a high liquid content, which are particularly difficult to be recycled or are unsuitable for energy regeneration via incineration. It is reported that full degradation of one piece of used diaper will take 500 years [68] . They thus become the major pollutants in landfills and undoubtedly a key source of primary microplastics.…”
Section: Introductionmentioning
confidence: 99%